(untitled) (Research, Society and Development, 2021)
Objective: Covid-19 is a highly infectious disease; it is transmitted by patients’ secretions and respiratory droplets SARS-CoV-2 was detected in patients saliva making dental care professionals more susceptible for contamination and the patient less safe while seeking the dental treatment. Methodology: This quantitative study was elaborated through a questionnaire for patients who frequently seek dental care in private and publica dental care units. A total of 205 over-18 patients were included, those who left one or more questions without answer were excluded. Participants were able to refuse to answer any question or to participate in the questionnaire at all. The questionnaire was composed of five questions. Participants were divided into two groups: Group 1: private dental offices patients (n=98); Group 2: public dental clinic patients (n=107). Results: there was a significant difference between groups 1 and 2, in which 50% of group 1 feel safe while seeking dental care during the Covid-19 pandemic in comparison with 72.89% of group 2. There was no significant difference between groups 1 and 2, in which 93.87 and 94.39% of groups 1 and 2 respectively feel safe with the professionals’ PPE and consider it sufficient. About 59.81% of the participants of group 2 do not feel insecure with the cross contamination caused by SARS-CoV-2 in collective health care units. Finally, there was a significant difference between groups 1 and 2, in which 74.48% of group 1 prefer to be attended by vaccinated professionals, instead of only 56.07% of group 2. Conclusion: it was concluded that not all dental patients feel safe while seeking dental treatment during the Covid-19 pandemic, however, they consider the professional PPE sufficient. Patients feel safe to be attended by vaccinated professionals.